The Legal Status and Operation of Unmanned Maritime Vehicles. (2nd January 2019) - Veal, Robert; Tsimplis, Michael; Serdy, Andrew
Abstract: The number of unmanned maritime vehicles (UMVs) and their potential applications in the marine space are growing constantly. Because of their comparatively small size and limited operations, only modest attention has been paid to how they fit into the international legal framework. Many UMVs may not be considered to fall under the definition of "ship" so as to enjoy states' rights of navigation under UNCLOS. Therefore states, manufacturers, and investors remain uncertain about the rights and obligations regarding UMV operations in the various maritime zones. This article addresses these questions for a range of UMVs with differing levels of autonomy. It argues that the international legal framework delegates the question of whether a UMV is a ship or not to the flag state's national laws. The article suggests that such a determination will be binding on other states. With respect to UMVs that do not fall under the definition of ship, there is remaining uncertainty about whether any navigational rights in the jurisdictional zones of other states are available, while it is argued that such rights do exist in the areas beyond national jurisdiction. The article also considers the extent to which today's UMVs can comply with the international framework for ensuring safety at sea. For those UMVs falling under the definition of ship, compliance with the current regulatory framework for shipping is required and compliance will be more difficult as the level of UMV autonomy increases.